Let’s HPC: A web-based platform to aid parallel, distributed and high performance computing education - Chaudhury, Bhaskar; Varma, Akshar; Keswani, Yashwant; Bhatnagar, Yashodhan; Parikh, Samarth (Journal of parallel and distributed computing, 2018)
Let’s HPC (www.letshpc.org) is an evolving open-access web-based platform to supplement conventional classroom oriented High Performance Computing (HPC) and Parallel & Distributed Computing (PDC) education. This platform has been developed to allow users to learn, evaluate, teach and see the performance of parallel algorithms from a system’s viewpoint. The Let’s HPC platform’s motivation comes from the experiences of teaching HPC/PDC courses and it is designed to help streamline the process of analyzing parallel programs. At the heart of this platform is a database archiving the performance and execution environment related data of standard parallel algorithm implementations run on different computing architectures using different programming environments. The online plotting and analysis tools of our platform can be combined seamlessly with the database to aid self-learning, teaching, evaluation and discussion of different HPC related topics, with a particular focus on a holistic system’s perspective. The user can quantitatively compare and understand the importance of numerous deterministic as well as non-deterministic factors of both the software and the hardware that impact the performance of parallel programs. Instructors of HPC/PDC related courses can use the platform’s tools to illustrate the importance of proper data collection and analysis in understanding factors impacting performance as well as to encourage peer learning among students. Scripts are provided for automatically collecting performance related data, which can then be analyzed using the platform’s tools. The platform also allows students to prepare a standard lab/project report aiding the instructor in uniform evaluation. The platform’s modular design enables easy inclusion of performance related data from contributors as well as addition of new features in the future. This paper summarizes the background and motivation behind the Let’s HPC project, the design philosophy of the platform, the present capabilities of the platform, as well as the plans for future developments. •An open platform to supplement conventional classroom oriented HPC and PDC education.•Allows in-depth performance analysis from a system’s perspective using over 20 parameters.•Facilitates variability analysis for each parameter using highly customizable plots.•Streamlines entire workflow using automated scripts and structured report generator.•Data Repository with performance data of many implementations and architectures.